Analisis Efisiensi Usahatani Cabai Rawit (Capsicum frutescens L.) Di Kabupaten Kotawaringin Barat - Novi Nurhayati; Eva Purnama Sari Sari (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2020)
Cayenne pepper is a horticultural crop, which is attracted by consumers. In Kotawaringun Barat Regency in the last 3 (three) years of chilli, production continues to increase, but it is not yet known whether the cultivation is technical, price or economically. The purpose of this research is to know the level of elasticity of production factors to the production of chilli pepper and know the level of technical efficiency, price, and economic farming chilli pepper in West Kotawarwant district. The research was conducted in Kotawaringin Barat District in December 2019 to February 2020. The number of samples used is 100 farmers respondent, with simple random sampling method. Data used by primary data and secondary data. Methods of data analysis using descriptive analysis, analysis of the Cobb-Douglass production function and analysis of technical efficiency, price/allocative, and economic. The results showed that the value of elasticity of the land area (0.501), seedlings (-0.201), fertilizer (0.112) and labour (0.386). The amount of elasticity 0.798 less than one indicates that chilli pepper farming is on a business scale (Decreasing return to scale), which contains the meaning of farming chilli pepper is not in the condition of a constant scale result. The value of technical efficiency (0.199), the value of the efficiency of the price/Alokatif (0.0031), the value of economic efficiency (0.0022), the third value of efficiency less than 1, meaning farming chilli pepper inefficient so that the need to reduce the use of production factors.